THE CORRELATION BETWEEN STUDENTS’ SELF-CONFIDENCE AND INTERPRETING ABILITY - I Gusti Agung Putri Wirastuti; Anak Agung Putu Arsana Putu Arsana; Dewa Ayu Ari Wiryadi Joni Ari Wiryadi Joni (Jurnal Santiaji Pendidikan (JSP), 2023)
Every research must have a purpose, as well as this study, which aims to determine the correlation between self-confidence and interpreting ability in seventh semester students of English Study Program at FKIP Unmas Denpasar. There were 27 students taken as a sample of class VII B with cluster sampling technique. This research was designed using correlation research. For data collection in this study, there were two instruments used, namely a questionnaire for a self-confidence test consisting of 30 items and an interpreting test. The collected data was then analyzed using Pearson's Product Moment Correlation on IBM SPSS Statistic 25. The results of the data analysis and based on statistical calculations obtained r of 0.617. From these results, it can be seen that there is a correlation between self-confidence and interpreting of the seventh semester of the English Language Study Program, FKIP Unmas Denpasar. In conclusion, the alternative hypothesis (Ha) is accepted.